Electronic Worksheets for Students on Conventional Biotechnology Kombucha to Improve Critical Thinking and Creativity Skills - Nurul Fadilah; Ixora Sartika Mercurian; Paidi (Universitas Negeri Yogyakarta, 2026)
This study develops an electronic Student Worksheet (LKPD) integrated with Project-Based Learning (PjBL) on conventional biotechnology material, specifically kombucha fermentation, to strengthen Phase E students’ critical thinking and creativity. The research is based on the limited mastery of 21st-century skills, particularly critical thinking and creativity, which remain challenges in schools. A Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was employed. The product underwent validation by media and material experts, followed by practicality testing with teachers and students. A limited trial in two Grade 10 classes involved questionnaires, observations, and tests. Data were analyzed descriptively and inferentially using MANOVA. Validation results indicated that the PjBL-based electronic LKPD is highly feasible in terms of content, technical quality, and presentation. Practicality testing also showed very good responses from teachers and students. Furthermore, MANOVA analysis confirmed a significant effect of the LKPD on improving both critical thinking and creativity simultaneously (Hotelling’s Trace, p < 0.05). In conclusion, the developed LKPD is feasible, practical, and effective as an innovative learning medium. It enhances critical thinking, fosters creativity, and contributes to the mastery of essential 21st-century competencies.